Sustainable development goals at local level, horticulture, and rural women: an experience in Restrepo - Colombia - karen Paola Duran; Jorge Luis Triana Riveros; Monica del Pilar Rodriguez Rodriguez (Revista Brasileira de Educação do Campo)
This article examines the role of rural women in La Floresta, Restrepo. These women, displaced by armed conflict, settled in this area with their families. The document aims to identify their role as social actors in food security and its connection to the SDGs of the 2030 Agenda in Floresta, Restrepo - Colombia. The methodology focused on a study case and was supported by quantitative and qualitative analysis through four phases (diagnosis, planning, execution, and evaluation). The main results prove that rural women in this area play a key role, handling tasks such as childcare, education, household management, and food production and preparation. They are wives, farm workers, mothers, and community leaders, actively taking part in decision-making and the planning of activities in rural projects. The results of the process show that rural women play a significant role in the department of Meta, promoting and transforming the territory and encouraging more women to participate in the development of their region.